Reversible and rewritable surface functionalization and patterning via photodynamic disulfide exchange - Du, Xin; Li, Junsheng; Welle, Alexander; Li, Linxian; Feng, Wenqian; Levkin, Pavel (Advanced materials, 2015)
A reversible surface functionalization and patterning strategy based on a photodynamic disulfide exchange reaction is demonstrated. The method allows for rapid and reversible functionalization, patterning, and exchange or removal of functional groups on the surface.